Marketing Strategy of a Chosen Company - Jedlička, Natalie; Volfová, Jitka, 1982-; Matysová, Kamila; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
This thesis is focused on the analysis of the marketing strategy of a chosen company. This work is divided into two parts. The theoretical and practical section. In the theoretical part, general information about the brand positioning, external analysis, marketing mix, and SWOT analysis is presented. In the practical part, the company is being introduced, after that, the brand positioning in the market and the marketing mix are being analysed. Moreover, the PESTEL and SWOT analysis are being conducted. In the end, the suggestions for improvement for the competitiveness of the company are mentioned.
Vedoucí práce: Jitka Volfová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses